Laparoscopic and robotic ureteral stenosis repair: a multi-institutional experience with a long-term follow-up. Issue 4 (December 2016) - Schiavina, Riccardo; Zaramella, Stefano; Chessa, Francesco; Pultrone, Cristian; Borghesi, Marco; Minervini, Andrea; Cocci, Andrea; Chindemi, Andrea; Antonelli, Alessandro; Simeone, Claudio; Pagliarulo, Vincenzo; Parma, Paolo; et al.
Abstract The treatment of ureteral strictures represents a challenge due to the variability of aetiology, site and extension of the stricture; it ranges from an end-to-end anastomosis or reimplantation into the bladder with a Boari flap or Psoas Hitch. Traditionally, these procedures have been done using an open access, but minimally invasive approaches have gained acceptance. The aim of this study is to evaluate the safety and feasibility and perioperative results of minimally invasive surgery for the treatment of ureteral stenosis with a long-term follow-up. Data of 62 laparoscopic (n  = 36) and robotic (n  = 26) treatments for ureteral stenosis in 9 Italian centers were reviewed. Patients were followed according to the referring center's protocol. Laparoscopic and robotic approaches were compared. All the procedures were completed successfully without open conversion. Average estimated blood loss in the two groups was 91.2 ± 71.9 cc for the laparoscopic and 47.2 ± 32.3 cc for the robotic, respectively (p  = 0.004). Mean days of hospitalization were 5.9 ± 2.4 for the laparoscopic group and 7.6 ± 3.4 for the robotic group (p  = 0.006). No differences were found in terms of operative time and post-operative complications. After a median follow-up of 27 months, the robotic group yielded 2 stenosis recurrence, instead the laparoscopic group shows no cases of recurrence (p  = 0.091). Minimally invasive approach for ureteral stenosis is safe and feasible. Both robotic and pure laparoscopic approaches may offer good results in terms of perioperative outcomes, low incidence of complications and recurrence.